(untitled) (ModaPalavra e-periódico, 2021)
This article approaches the innovation processes in clothing industry in order to analyse how collaboration among stakeholders may generate value and innovation. At first, a Bibliographic Review outlines the theoretical framework on which the subject is based and empirically proved through a Case Study held in a Brazilian company. The results presented and discussed herein disclose new aspects on facts which give rise to value and innovation. This study lead to the conclusion of two casual relationships in clothing product development: the creative and collaborative process between different stakeholders, in this study denominated codesign, is essential for value generation as relationship management is for innovation.